Changes in cardiac sympathetic nerve activity on 123I‐metaiodobenzylguanidine scintigraphy after MitraClip therapy. (19th February 2021) - Fukuda, Keisuke; Hasegawa, Seiji; Kawamura, Tomonori; Waratani, Naoto; Hirata, Kumiko; Higashimori, Akihiro; Yokoi, Yoshiaki
Abstract: Aims: In patients with heart failure, over‐activation of the cardiac sympathetic nerve (CSN) function is associated with severity of heart failure and worse outcome. The effects of MitraClip therapy on the CSN activity in patients with mitral regurgitation (MR) remained unknown. In this study, we evaluated the impact of the MitraClip therapy on CSN activity assessed by 123 I‐metaiodobezylguanidine (MIBG) scintigraphy. Methods and results: We enrolled consecutive patients with moderate‐to‐severe (3+) or severe (4+) MR who were scheduled to undergo MitraClip procedure in this prospective observational study. MIBG scintigraphy was performed at baseline and 6 months after the MitraClip procedure to evaluate the heart–mediastinum ratio and washout rate (WR). Changes in these MIBG parameters were analysed. Of the 13 consecutive patients, 10 were successfully treated with MitraClip procedure and completed follow‐up assessment. With regard to the MIBG parameters, changes in the early and delayed heart–mediastinum ratio from baseline to 6 months were not significant (2.16 ± 0.42 to 2.06 ± 0.34, P = 0.38 and 1.87 ± 0.39 to 1.83 ± 0.39, P = 0.43, respectively), whereas WR was significantly decreased (38.6 ± 3.9% to 32.6 ± 3.94%, P = 0.002). Conclusions: The CSN activity of the WR on MIBG imaging was improved 6 months after MitraClip therapy in patients with 3+ or 4+ MR.